INTEGRATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING METHODS IN THE 21st CENTURY AT MA NAHDHOTUT THOLIBIN - Nurkholes, Muhammad; Pramuja, Alvin Dian (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
In facing education challenges in the modern era, Islamic Religious Education (PAI) learning at MA Nahdlotut Tholibin seeks to integrate religious values relevant to the times' needs. The PAI curriculum, which still uses many traditional methods, is considered less effective in attracting the interest of students who grow up in the era of globalization, which further erodes moral and ethical values. Surveys conducted in several educational institutions found that although students understand religious concepts, they often have difficulty implementing them in real life. This research aims to develop a more relevant and applicable learning methodology which is theoretical and supports the practice of students' daily lives. This study uses a descriptive qualitative approach by conducting in-depth interviews, classroom observations, and document analysis to evaluate the application and suitability of 21st-century learning methods. Participants in this study include PAI teachers, students, and administrators from MA Nahdlotut Tholibin. The data was analyzed using content analysis techniques. The study results show that learning methods with 21st-century skills such as Communication, Collaboration, Critical Thinking and Problem Solving, and Creativity and Innovation can increase students' understanding and motivation to learn. This approach helps students become critical thinkers and practitioners of good religious values in modern society. This research provides insight into the importance of designing a curriculum responsive to changing times. It supports the development of students' interpersonal skills and strengthens their ability to integrate religious teachings into daily decision-making.